Contribution of Infectious Agents to the Development of Celiac Disease - Sánchez, Daniel; Hoffmanová, Iva; Szczepanková, Adéla; Hábová, Věra; Tlaskalová-Hogenová, Helena (Microorganisms, 2021)
The ingestion of wheat gliadin (alcohol-soluble proteins, an integral part of wheat gluten) and related proteins induce, in genetically predisposed individuals, celiac disease (CD), which is characterized by immune-mediated impairment of the small intestinal mucosa. The lifelong omission of gluten and related grain proteins, i.e., a gluten-free diet (GFD), is at present the only therapy for CD. Although a GFD usually reduces CD symptoms, it does not entirely restore the small intestinal mucosa to a fully healthy state. Recently, the participation of microbial components in pathogenetic mechanisms of celiac disease was suggested. The present review provides information on infectious diseases associated with CD and the putative role of infections in CD development. Moreover, the involvement of the microbiota as a factor contributing to pathological changes in the intestine is discussed. Attention is paid to the mechanisms by which microbes and their components affect mucosal immunity, including tolerance to food antigens. Modulation of microbiota composition and function and the potential beneficial effects of probiotics in celiac disease are discussed.
Keywords: celiac disease; microbiota; parasites; infections; immune response; gluten-free diet